Threat assessment analysis for vehicle collision avoidance - Mohammad Izzad, Mohammad Idzlaluddin (2017)
This thesis presents a threat assessment analysis for collision avoidance just before an accident. This is due to the high rate of accidents that happened in Malaysia for the past years. The outcome of this research is to simulate the vehicle's maneuver trajectory to prevent accidents. Besides that, possible impacts of the accidents will be estimated for threat assessment analysis. This project also provides an appropriate decision making for the driver by assessing different vehicle's maneuver conditions. There are different cases of avoidance such as the driver of a vehicle can use braking, acceleration or steering to avoid a collision with an obstacle model. An intelligent threat analysis is proposed to estimate the possible position of the main vehicle to generate a minimum impact force of potential accidents. The analysis proposed will help the driver to make decision to avoid an obstacle. In addition, the environment uses MATLAB/Simulink for simulation to estimate the position. The simulation includes system blocks of vehicle dynamics, kinematics of a car and obstacle modelling. Simulation results and theoretical value of impact forces are able to determine the suitable position of vehicle to avoid obstacles.